Developing an Instructional Model for Teaching Mak Yong Theater in Cultural Arts Education: A Qualitative Case Study - Novi Yanti; Agusti Efi (Journal of Education Research, 2026)
The traditional Mak Yong theater is a rich cultural heritage with distinctive aesthetic and symbolic values; however, its teaching in schools remains limited. This study aims to describe the learning strategies for teaching Mak Yong theater within the Cultural Arts curriculum and to explore their influence on students’ technical skills, creativity, and cultural understanding. A qualitative approach was employed, including classroom observation, semi-structured interviews with teachers and students, documentation, and reflective analysis of teacher-student interactions. The findings reveal that a staged instructional strategy comprising cultural introduction, movement and vocal practice, role playing, reflection, mini-performances, and collaborative evaluation supports the development of students’ technical abilities, creative engagement, collaboration, and appreciation of cultural heritage. While the results suggest positive learning outcomes, they are context-specific and exploratory; further research is needed to examine the strategy’s effectiveness across different educational settings. The study highlights the potential of integrating traditional Mak Yong theater into school curricula to foster cultural awareness and preserve this heritage for younger generations.